Quality Management–Based Marketing Strategy for Kombucha ‘Rumah SCOBY DBA’: A Study at Yayasan Dharma Bintang Akademia - Hari Mulia; Suca Rusdian; Junaedi Junaedi; Andri Muhamad Nuroni; Mia Kusmiati; Yeti Rosita; Dini Nurhayati; Sovian Aritonang; Avinash Pawar (Global Management: International Journal of Management Science and Entrepreneurship, 2024)
This study analyzes the strategic role of quality-based marketing models in enhancing the competitiveness of kombucha products, with a specific focus on Rumah SCOBY DBA, produced by the Yayasan Dharma Bintang Akademia. By integrating Total Quality Management (TQM), Quality Assurance (QA), and Quality Control (QC), the research explores how quality-driven frameworks contribute to marketing effectiveness, consumer trust, brand positioning, and sustainable performance in the functional beverage industry. Employing a Systematic Literature Review (SLR) combined with conceptual analysis, the study systematically examined publications from 2015 to 2025 across leading academic databases, focusing on themes of quality management, functional beverage marketing, kombucha production, consumer behavior, and digital strategies. The findings reveal that product quality—characterized by fermentation stability, microbiological safety, and nutritional consistency—serves as the primary driver of consumer purchase intention. Process quality, through standardized SOPs, hygiene protocols, and traceability systems, reinforces credibility, while service quality, including transparent labeling, health education, and digital engagement, strengthens brand trust. Integrating TQM principles into marketing fosters consumer loyalty, differentiates brands in competitive markets, and supports long-term sustainability. This study provides practical guidance for producers, community-based enterprises, and policymakers to adopt quality-driven marketing models, offering a novel conceptual framework tailored to kombucha products and mapping future research directions in functional beverage innovation.